Transcriptomic analysis of the differentiating ovary of the protogynous ricefield eel Monopterus albus - Jinfeng Cai; Wei Yang; Dong Chen; Yize Zhang; Zhi He; Weimin Zhang; Lihong Zhang (BMC Genomics, 2017)
Abstract Background The ricefield eel is a protogynous hermaphroditic Synbranchiform species that changes sex naturally from female to male, which offers an interesting model for studying gonadal (particularly ovarian) differentiation in vertebrates. In the present study, transcriptome sequencing of the gonad of ricefield eel larvae was performed to explore the molecular mechanisms underlying the ovarian differentiation and development. Results A total of 301,267,988 clean reads were generated from cDNA libraries of gonadal tissues of ricefield eel larvae at 6, 9, 12, and 20 days post hatching (dph), which contained undifferentiated gonads, differentiating ovaries, ovaries with oogonia, and ovaries with meiotic oocytes, respectively. De-novo assembly of all the clean reads generated a total of 265,896 unigenes with a mean size of 720 bp and a N50 of 1107 bp. RT-qPCR analysis of the developmental expression of 13 gonadal development-related functional genes indicated that RNA-seq data are reliable. Transcriptome data suggest that high expression of female development-related genes and low expression of male development-related genes in the early gonads of ricefield eel larvae participate in the cascade of sex differentiation leading to the final female phenotype. The contrasting expression patterns of genes involved in retinoid acid (RA) synthesis and degradation might result in peak production of RA at 12 dph in the gonad of ricefield eel larvae, and induce molecular events responsible for the initiation of meiosis before the meiotic signs could be observed at 20 dph. In addition, only stra6 but not stra8 could be identified in gonadal transcriptome data of ricefield eel larvae, and the expression pattern of stra6 paralleled those of genes involved in RA synthesis, suggesting that stra6 may be a downstream target of RA and play a role in RA metabolism and/or meiotic initiation in the gonad of ricefield eel larvae. Conclusions The present study depicted the first large-scale RNA sequencing of the gonad of ricefield eel larvae, and identified many important functional genes, GO terms and KEGG pathways involved in gonadal development and germ cell meiosis. Results of the present study will facilitate future study on the ovarian differentiation of ricefield eels and other teleosts as well.